Poe's pervasive influence - Cantalupo, Barbara (Bethlehem, PA : Lehigh University Press, 2012)
Complementing and extending a project begun by Lois Vines' Poe Abroad (University of Iowa Press, 1999), Poe's Pervasive Influence includes essays on Poe's influence abroad from Japanese author, Edogawa Rampo, to Russian author, Nikolai Gogol, and takes a wider perspective on Poe's influence by including essays on Poe's impact on American authors from Harriet Jacobs to Joyce Carol Oates.
Pathologizing modernity: the grotesque in Poe and Rampo / Seth Jacobowitz -- Visionary media in Edgar Allan Poe and Edogawa Rampo / William O. Gardner -- Poe's shadow in Japan: alternative worlds and failed escapes in Edogawa Rampo's The strange tale of Panorama Island / Mark Silver -- Interview with Kiyoshi Kasai / Barbara Cantalupo -- Lu Xun and Poe: reading the psyche / Diane M. Smith -- "Breaking the law of silence": rereading Poe's "the man of the crowd" and Gogol's "The portrait" / Alexandra Urakova -- "What has occurred that has (never) occurred before": a case study of the first Portuguese detective story / Isabel Oliveira Martins -- "Around reason feeling": Poe's impact on Fernando Pessoa's modernist proposal / Margarida Vale de Gato -- Poe in place / Charles Cantalupo -- Ligeia-not me!: Three women writers respond to Poe / Daniel Hoffman -- Gothic windows in Poe's narrative space / Shoko Itoh -- Poe's progeny: varieties of detection in key American literary texts, 1841-1861 / John Gruesser.
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Poe, Edgar Allan, -- 1809-1849 -- Influence; Poe, Edgar Allan, -- 1809-1849 -- Criticism and interpretation; Poe, Edgar Allan, -- 1809-1849; LITERARY CRITICISM -- American -- General; Influence (Literary, artistic, etc.); Criticism, interpretation, etc